Across the Frontiers: Impact of Foreign Journals in Library Science in India: A Citation Analysis - Gopinath, M. A. (Journal of Information and Knowledge, 1993)
Presents a citation analysis of the foreign library science journals by the Indian library science authors. The data indicate that the United States of America being the largest publishers of library science literature, have the largest impact. The United Kingdom is the second most cited country. The data is gathered out of a cross-section of publications published during the last five years.